Synergistic Effect of Pleuromutilins with Other Antimicrobial Agents against Staphylococcus aureus In Vitro and in an Experimental Galleria mellonella Model - Dong, Chun-Liu; Li, Lin-Xiong; Cui, Ze-Hua; Chen, Shu-Wen; Xiong, Yan Q.; Lu, Jia-Qi; Liao, Xiao-Ping; Gao, Yuan; Sun, Jian; Liu, Ya-Hong (Frontiers in Pharmacology, 2017)
Invasive infections due to S. aureus, including methicillin-resistant S. aureus (MRSA) are prevalent and life-threatening. Combinations of antibiotic therapy have been employed in many clinical settings for improving therapeutic efficacy, reducing side effects of drugs, and development of antibiotic resistance. Pleuromutilins have a potential to be developed as a new class of antibiotics for systemic use in humans. In the current study, we investigated the relationship between pleuromutilins, including valnemulin, tiamulin and retapamulin, and 13 other antibiotics representing different mechanisms of action, against methicillin-susceptible and -resistant S. aureus both in vitro and in an experimental Galleria mellonella model. In vitro synergistic effects were observed in combination of all three study pleuromutilins with tetracycline by standard checkerboard and/or time-kill assays. In addition, the combination of pleuromutilins with ciprofloxacin or enrofloxacin showed antagonistic effects, while the rest combinations presented indifferent effects. Importantly, all study pleuromutilins in combination with tetracycline significantly enhanced survival rates as compared to the single drug treatment in the Galleria mellonella model caused by S. aureus strains. Taken together, these results demonstrated synergy effects between pleuromutilins and tetracycline against S. aureus both in vitro and in vivo.